Inkonsistensi Struktur dan Makna Backronim pada Tagline Universitas Al Azhar Indonesia - Hadiansyah, Dhuha; Bawarti, Era; Sabbah, Sherien; Herwandar, ria (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
Backronyms play an important role in branding by creating taglines that strengthen brand identity and build emotional connections, supporting effective marketing strategies. For universities as socialpreneurship or edupreneurship entities, the use of backronyms can enhance visibility and attract prospective students, helping to achieve long-term goals. This study analyzes the backronyms "SMILE" and "UNGGUL" from University Al-Azhar of Indonesia to evaluate their structural and semantic coherence. Using a qualitative approach, it was found that the "SMILE" backronym exhibits inconsistency between adjectival and nominal word classes, which disrupts both cohesion and overall meaning. Meanwhile, the "UNGGUL" backronym presents a more complex misalignment, involving verbs, nouns, and adjectives, leading to morphological and semantic discord as well as logical flaws. The conclusion of this study is that the inconsistency in word class usage and the illogical semantic connections diminish the communicative effectiveness of the backronyms, suggesting the need for improvements in backronym construction to enhance clarity and appeal in the university's branding strategy.Keywords - Backronym, Morphological Analysis, Semantic Consistency, Tagline.